Pengenalan WebGIS dalam Pendidikan Geografi SMA di Sukoharjo - Wardhani, Puspita Indra; Nurhafida, Siti Hadiyati; Wibowo, Yunus Aris (Universitas Muhammadiyah Surakarta, 2024)
The learning media are needed to support teaching and learning activities during the Covid 19 pandemic. The pandemic condition caused limited teaching and learning activities in class. The situation made the learning activity becomes an online class. Geography is one of the subjects that is affected by the situation. Geography learning activities need direct explanation and practice. So the students can understand easily. The learning media using WebGIS technology can offer a solution to overcome these limitations. WebGIS can be operated online with interactive menus. Both teachers and students can do together in the learning activities. This study purposed to introduce WebGIS to support geography subjects in online classes. The development of GIS technology is currently moving very fast and is leading to a web form. Geography Education teachers need to know and know what GIS is to stay abreast of technological developments. In collaboration with the Geography MGMP in Sukoharjo Regency, this activity was carried out to introduce WebGIS to teachers and upgrade the GIS material.